Squash Bug, Anasa tristis (DeGeer) (Insecta: Hemiptera: Coreidae) - John L. Capinera (EDIS)
The squash bug, Anasa tristis, attacks cucurbits (squash and relatives) throughout Central America, the United States, and southern Canada. Several related species in the same genus coexist with squash bug over most of its range, feeding on the same plants but causing much less injury. This document is EENY-077, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 1999. Revised: November 2001.